Headstands, Writing, and the Rhetoric of Radical Self-Acceptance - Geraldine DeLuca (Journal of the Assembly for Expanded Perspectives on Learning, 2005)
By emphasizing the importance of patient practice as an end in itself, yoga offers a model teaching and learning writing that can help students move forward in a context of self-acceptance and find the sources of their own talents and values.